Rearing of the banded fruit weevil, Phlyctinus callosus (Schonherr) (Coleoptera: Curculionidae) and control with entomopathogenic nematodes - Ferreira, Tiarin (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScAgric (Conservation Ecology and Entomology))--University of Stellenbosch, 2010.